The Relationship between Communication Skills with Aggression and Perfectionism of Lifeguards - Abbas Khodayari; Farideh Hadavi; Mohammad Javad Barzegar Mohammadi (The Society of Aging and Physical Activity (SAPA), 2015)
The purpose of the present study was to determine the relationship between aggression and perfectionism with communication skills of male lifeguards in Tehran. For this purpose, 300 qualified lifeguards from which 169 persons were selected as the study sample. In order to conduct this study, Aggression Questionnaires (Buss and Perry 1992), Positive and Negative Perfectionism Questionnaire (Terry-Short et al., 1995), Communication Skills Questionnaire (Stacey et al. 2006) were used. The results of the study showed that there is no relationship between aggression and its subscales with communication skills, except with hostility (r=0.169, p0.05). The study also showed that there is no relationship between positive and negative perfectionism and communication skills' components, except between positive perfectionism with audio communication skills (r=-0.194, p0.05); and there are no multiple correlations between aggression and perfectionism with communication skills of male lifeguards in Tehran. It is concluded that proper use of aggression, perfectionism and communication skills can be used in identifying and selecting lifeguards.